Development of an immunochromatographic strip for the rapid detection of 10 β-agonists based on an ultrasensitive monoclonal antibody. Issue 4 (4th July 2017) - Liu, Rui; Liu, Liqiang; Song, Shanshan; Cui, Gang; Zheng, Qiankun; Kuang, Hua; Xu, Chuanlai
ABSTRACT: A sensitive monoclonal antibody, 3G10, derived from a mouse immunized with an immunogen of salbutamol hapten conjugated to keyhole limpet hemocyanin was developed against β-agonists, with a view to establishing a rapid gold nanoparticle immunochromatographic strip. The antibody displayed a 50% inhibitory concentration (IC50 ) of 1.04 ng/mL for salbutamol and simultaneously detected nine other β-agonists (clenbuterol, cimatero, brombuterol, mabuterol, terbutaline, clenpenterol, carbuterol, mapenterol, pirbuterol) with uniform cross-reactivity. The immunochromatographic strip had cut-off values of 5 ng/mL for salbutamol and clenbuterol, 20 ng/mL for cimaterol, brombuterol and mabuterol, and 50 ng/mL for terbutaline, clenpenterol, carbuterol, mapenterol and pirbuterol. The collective advantages of the newly developed strip, such as high affinity, sensitivity and rapidity, support its utility in detecting β-agonists from actual biological samples, such as urine.